PENGARUH PEMAHAMAN PAJAK TERHADAP KUALITAS LAPORAN KEUANGAN UMKM DI BENGKULU - Seventeen, Winny Lian; Perdanakusuma, fathul Hilal (PARETO : Jurnal Ekonomi dan Kebijakan Publik, 2025)
Micro, Small, and Medium Enterprises (MSMEs) have a strategic role in the Indonesian economy, including in Bengkulu, with a large contribution to the Gross Regional Domestic Product (GRDP) and employment. However, many MSMEs in Bengkulu face challenges in financial management and taxation, especially related to low tax understanding. This study aims to examine the effect of tax understanding on the quality of MSME financial reports in Bengkulu. A quantitative approach with a survey method was used to collect data through questionnaires from registered MSME owners. The research variables include tax understanding as an independent variable and financial report quality as a dependent variable, with controls in the form of business scale, owner education level, and use of accountant services. The results of the study indicate that tax understanding has a significant positive effect on the quality of MSME financial reports, with a coefficient of determination (R²) of 0.451. This finding indicates that a good understanding of tax obligations can improve the accuracy and transparency of MSME financial reports. This study provides a practical contribution to MSME actors and local governments in designing policies to improve tax literacy and support sustainable economic growth in Bengkulu.Send feedbackSide panelsHistorySaved